The Effect Of Reizuka Ari’s Credibility, Attractiveness, And Brand Preference On Skincare Purchase Intention Among Gen Z in Surabaya - Ayu Febrini Putri; Muhammad Fachmi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The increasing popularity of social media has made influencer marketing an important strategy for influencing consumers’ purchase intention, particularly among Generation Z. In the skincare industry, influencers play a significant role in shaping consumers’ purchasing decisions through their credibility, attractiveness, and ability to build brand preference. This study aims to examine the influence of influencer credibility, influencer attractiveness, and brand preference on skincare purchase intention among Generation Z in Surabaya, using Reizuka Ari as the research context. This study employed a quantitative research approach using a purposive sampling technique involving two hundred Generation Z respondents in Surabaya who had watched skincare related content created by Reizuka Ari on TikTok. Data were collected through an online questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics version 27 after passing validity, reliability, and classical assumption tests. The results reveal that influencer credibility, influencer attractiveness, and brand preference each have a positive and significant partial effect on purchase intention, with brand preference emerging as the strongest predictor. These findings indicate that strengthening brand preference while collaborating with credible and attractive influencers can effectively enhance skincare purchase intention among Generation Z in Surabaya.